Benefits of WhatsApp as a Communication Media on Small Business Social Networks - Neny Lara Amiati Sugiyantoro; Mahendra Wijaya; Supriyadi Supriyadi (The Journal of Society and Media, 2022)
The production and marketing processes in small businesses are supported by social networks. These social networks are supported by good communication. During the Covid-19 pandemic, the use of WhatsApp as a social media was a solution to communicating online. This study aims to analyze the benefits of WhatsApp as a communication media on the social network of the Farizka Fashion jeans convection business. This study uses a social network theory. This research used qualitative method with a case study strategy. The research informants were determined based on purposive sampling technique. The research informants consisted of one key informant, ten main informants, and one supporting informant. Primary data were obtained through non-participant observation and in-depth interviews, while secondary data were obtained through documentation. The validity of the research data used triangulation of data sources. Data analysis technique used interactive model. The results of this research are the benefits of WhatsApp as a communication media on the social network of the Farizka Fashion jeans convection business in the production sector, namely WhatsApp group is used to communicate about work and build a social relation